Pengaruh Good Corporate Governance terhadap Harga Saham Perusahaan Manufaktur Periode 2017-2022 - Arifin, Adhyasta Izhar Resvara; Rosidi, Rosidi (Studi Akuntansi dan Keuangan Indonesia, 2024)
This study aims to investigate the influence of several proxies of Good Corporate Governance (GCG), namely Foreign Ownership, Institutional Ownership, Board of Commissioners, and Audit Committee, on the stock prices of manufacturing sector companies. The research sample consists of 45 manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2017-2022. The sampling technique used is purposive sampling, and the final sample obtained is 45 companies. The analysis method employed in this study is multiple linear regression analysis conducted using IBM SPSS 25 software. The results of the study indicate that Institutional Ownership and the Board of Commissioners have a positive influence on the company's stock price. This suggests that the larger the institutional ownership and the more effective the function of the board of commissioners, the more likely the stock price will increase. Conversely, the study found that Foreign Ownership and the Audit Committee do not have a significant impact on stock prices. This means that even if a company has high foreign ownership or an active audit committee, these factors do not directly affect the fluctuations in the company's stock price. TRANSLATE with x English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster Portal Back //